The prospective multiple-centre randomized controlled clinical study of high-dose amoxicillin-proton pump inhibitor dual therapy for H. pylori infection in Sichuan areas. (31st December 2022) - Shen, Cheng; Li, Changping; Lv, Muhan; Dai, Xiaosong; Gao, Caiping; Li, Liangping; Zhang, Qin; Pan, Wen; Liu, Chao; Han, Sijing; Zhang, Yang; Ding, Shunbin; et al.
Abstract: Objectives: To evaluate the safety and efficacy of high-dose amoxicillin-proton pump inhibitor dual therapy, and to provide a new eradication regimen as a first-line option for patients with H. pylori infection. Methods: A total of 971 H. pylori positive patients who received initial treatment were recruited from March to August 2020, and randomly divided into treatment group and control group. The treatment group received of 20 mg esomeprazole four times daily and 750 mg amoxicillin four times daily for 14 days. Control group received of 220 mg bismuth potassium citrate twice daily, 20 mg esomeprazole twice daily, 1000 mg amoxicillin twice daily and 250 mg clarithromycin capsule twice daily for 14 days. Four weeks after the end of treatment, the urea breath test was reviewed to detect whether H. pylori was eradicated. Results: There were no statistical differences in age, gender, the total clinical symptom scores before and after initial treatment, the compliance, and the degree of remission of symptoms before and after initial treatment between the two groups. The eradication rates of H. pylori between dual therapy and quadruple therapy were 88.31% and 85.26% ( p =.158) by intention-to-treat (ITT) analysis, 88.66% and 85.44% ( p =.186) by modified intention-to-treat (mITT) analysis, and 91.63% and 90.60% ( p =.116) by PP analysis, respectively. Adverse events in dual therapy group were significantly lower than quadruple therapy group (13.3% vs. 28.2% ( p <.01)). Conclusions: For the initial treatment of H. pylori infection, the high-dose dual therapy regimen has the same efficacy as the bismuth-containing quadruple therapy regimen, good compliance, less adverse reactions and high safety, so it can be recommended as the empirical first-line treatment regimen for the eradication of H. pylori (KY2019173).